أحباس جربة: أزمة مؤسسة أم تحول مجتمع محلي - الباهي, مبروك (Les Iles Méditerranéennes: relais de civilisations : actes de colloque international collectif, 2004)
Keywords: Famille Bin Ayyad; Hadharbash, mosquée (Midoun, Djerba); Jadariyya, mosquée al- (Jaabira, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Waqf (fondations) -- Djerba

Djerba, Saint-Hippolyte et le Stadiasme - Desanges, Jehan (Les Iles Méditerranéennes: relais de civilisations : actes de colloque international collectif, 2004)
Keywords: Antiquité; Waqf (fondations) -- Djerba

A propos de gravures récentes dans le M’Zab (Sahara algérien) - Ferhat, Nadjib (Valcamonica Symposium, 2004)
Au cœur de la vallée du M’Zab à quelques 600 kilomètres au Sud du littoral méditerranéen, et au cours de récentes extensions sur le plateau du Belvédère de la ville de Béni Isguen, une des cinq villes de la pentapole de Ghardaïa, de nouvelles gravures rupestres, ont été mises en évidence. Les gravures, dites du Belvédère, se trouvent sur des dalles horizontales, formant le sommet d’une surface de plateau qui s’étire en un promontoire rocheux qui domine de la ville à son côté oriental. Ce site est destiné à la construction d’un nouveau lotissement de plus de 500 logements sur une superficie de 14 hectares. Un premier inventaire photographique des gravures, limité à la surface du lotissement à bâtir, a pu mettre en évidence une centaine de gravures toutes symboliques réparties sur 80 dalles horizontales. Cette découverte est un ensemble original dont on ne connaît aucun similaire dans tout le Sahara. Leur symbolisme et leur mode d’obtention permettent de soutenir leur appartenance à une époque récente au plus vieux remontant à l’âge du bronze. Les gravures du Belvédère sont d’une importance première pour la connaissance de l’évolution de l’art rupestre saharien notamment celui des époques “tardives“ ainsi que celui du peuplement, à ces mêmes époques, de la vallée du M’Zab, d’autant que le site gravé est situé à quelques centaines de mètres de l’enceinte de la ville de Béni Isguen juste sur la rupture de pente de la rive gauche de l’oued N’Tissa, un des affluents de l’Oued M’Zab.
Keywords: Art rupestre -- Mzab

From Sacrilege to Sacrifice. Observations on Violent Death in Classical and Modern Arabic Poetry - Neuwirth, Angelika (Martyrdom in Literature: Visions of Death and Meaningful Suffering in Europe and the Middle East from Antiquity to Modernity, 2004)
Keywords: poésie kharijite

قصيدة الرثاء في شعر أحمد بن عبد الله الحارثي: بين نمطية التعبير والبحث عن رؤيا - الحارثي, جوخة (دراسات في أدب عمان والخليج, 2004)
Keywords: Poésie -- Oman

الربع الخالي في الأدب الإنجليزي: نصوص شعرية - الحجري, هلال بن سعيد (دراسات في أدب عمان والخليج, 2004)
Keywords: Récits de voyage -- Oman

مدخل إلى أدب الرحلات في عمان: دراسة وصفية للرحالة البريطانيين 1627-1970 - الحجري, هلال بن سعيد (دراسات في أدب عمان والخليج, 2004)
Keywords: Récits de voyage -- Oman

عبد لببه الطائي وريادة الأدبية الأولي العمانية الحديثة - الكندي, محسن (دراسات في أدب عمان والخليج, 2004)

أبو مسلم البهلاني: رائد الشعر العماني الحديث - المحروقي, محمد (دراسات في أدب عمان والخليج, 2004)
Keywords: Poésie -- Oman

تحليل الخطاب الروائي النسوي العماني: رواية الطواف حيث الجمر نموذجا - اليحيائي, شريفة خلفان (دراسات في أدب عمان والخليج, 2004)

تجليات المكان والزمان في القصة العمانية القصيرة - ميدان, أيمان (دراسات في أدب عمان والخليج, 2004)
Keywords: Littérature -- Oman

Un curieux ensemble sculpté de l'Afrique romaine: les piliers de Meninx - Baratte, François; Ouertani, N. (Studi di archeologia in onore di Gustavo Traversari, 2004)
Keywords: Archéologie -- Djerba

From Arzuges to Rustamids: State formation and Regional Identity in the Pre-Saharan Zone - Rushworth, Alan (Vandals, Romans and Berbers: new perspectives on late antique North Africa, 2004)
Keywords: Dynastie rustumide

From Donatist opposition to Byzantine loyalism: The Cult of Martyrs in North Africa 350-650 - Frend, William (Vandals, Romans and Berbers: new perspectives on late antique North Africa, 2004)
Keywords: Donatisme

Who were the circumcellions - Shaw, Brent D. (Vandals, Romans and Berbers: new perspectives on late antique North Africa, 2004)
Keywords: Donatisme

Italian Archaeology in Libya: From Colonial Romanita to Decolonization of the Past - Munzi, Massimiliano (Archaeology under dictatorship, 2004)
Keywords: Archéologie -- Djebel Nefousa

Italian Colonial Archaeology in Libya 1912-1942 - Altekamp, Stefan (Archaeology under dictatorship, 2004)
Keywords: Archéologie -- Djebel Nefousa

The press: engine of a mini-renaissance in Zanzibar (1860-1920) - Sadgrove, Philip C. (History of printing and publishing in the languages and countries of the Middle East, 2004)
Keywords: Imprimerie -- Zanzibar

The adventures of Abū Ḥārith: Muslim travel writing and navigating the modern in colonial East Africa - Reese, Scott Steven (The transmission of learning in Islamic Africa, 2004)
Keywords: Zanzibar

A survey of Arabic-character publications printed in Egypt during the period 1238-1267 (1822-1851) - Hsu, Cheng-Hsiang (History of printing and publishing in the languages and countries of the Middle East, 2004)
Keywords: Bibliographie

Zanzibar. Some nineteenth-century Arabic writings on healing - Declich, Lorenzo (The transmission of learning in Islamic Africa, 2004)
Much on Emily Said-Ruete’s Memoirs of an Arabian princess. Then on MSS and books on tradtional medicine and magic, found in the Zanzibar National Archives.
Keywords: Catalogue -- Zanzibar

An overview of Ibāḍī Tafsīr - Kharusi, Kahlan al- (Islamic reflections Arabic musings: Studies in Honour of Professor Alan Jones, 2004)
An exhaustive overview of Ibāḍī works on Koran interpreting. The author concludes his article saying, pending more detailed studies, that Ibāḍī Tafsīr falls in the middle of two extremes. On the one hand, the Muʿtazila, who over-used al-ʿAql (rationality, reasoning) in interpreting the Koran, and on the other hand the many Sunnīs who rely largely on al-Naql (tradition or irrationality).
Keywords: Coran -- Commentaires

Werner Vycichl (1909-1999)-biographical sketch - Takács, Gábor (Egyptian and Semito-Hamitic (Afro-Asiatic) studies: in memoriam W. Vycichl, 2004)
Keywords: Linguistique -- Djerba

min Aʿlām Buhlà - Shaybānī, Sulṭān b. Mubārak (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)

al-Buʿd al-Jughrāfī li-Wilāyat Buhlà - Laythī, Māhir al- (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)

Buhlà ʿinda ‘l-Udabā’ wa’l-Shuʿarā’ wa’l-Raḥḥālīn - Haykal, Samīr (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)

Malāmiḥ min Tārīkh Buhlà - Ghaylānī, Saʿīd b. Muḥammad b. Saʿīd al- (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)

Muqaddima fī Maʿālim Buhlà al-Ḥaḍāriyya - Būsaʿīdī, Yaʿqūb b. ʿAbdallāh al- (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)

al-Ḥayāt al-Fikriyya fī Buhlà khilāla ‘l-Fatra min 800-1050 H. (al-Usra al-Mufarrajiyya Namūdhajan) - ʿAdawī, Khamīs b. Rāshid b. Suʿayyid al- (Buhlà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Buhlà, Yawmay al-Arbaʿā’ wa’l-Khamīs 23-24 Shaʿbān 1423/30-31 Oct. 2002, 2004)
Keywords: Vie intellectuelle -- Oman

From Wadi Mizab to Unguja: Zanzibar’s Scholarly Links - Sadgrove, Philip C. (The transmission of learning in Islamic Africa, 2004)
Keywords: Zanzibar

Mohamed Ben Smaïl : entretien - Camau, Michel; Geisser, Vincent; Ben Smaïl, Mohamed (Habib Bourguiba: la trace et l'héritage, 2004)

Ibāḍī publishing Activities in Cairo, c. 1880-1960s - Custers, Martin H. (Ultra mare: mélanges de langue arabe et d'islamologie offerts à Aubert Martin, 2004)
Keywords: Bibliographie